Aptamer-mediated targeting of CXCR3-B in acute lymphoblastic leukemia nalm-6 cells: an in silico and in vitro study - Hossein Arezoomand; Ali Jebali; Hajar Mardani Valandani; Maryam Nooshadokht; Ali Bazi; Ali Afgar; Muhammad Hossein Ashoub; Roohollah Mirzaee Khalilabadi (Molecular Biology Reports, 2026)

Lutein reverses M2 macrophages polarization and exhibits antitumor effects on human triple-negative breast cancer cells - Redzyque Ramza Ramli; Siti Nur Hasyila Muhammad; Maryam Azlan; Asma Abdullah Nurul; Siti Norasikin Mohd Nafi; Agustine Nengsih Fauzi (Molecular Biology Reports, 2026)

Neuroprotective effect of Continentalic acid by targeting NF-κB/Bcl-2 and oxidative stress signaling in traumatic brain injury in male BALB/c mice - Sana Zafar; Maryam Jamil; Muhammad Ibrar Khan; Ashraf Ullah Khan; Kifayat Ullah Shah; Eun Kyoung Seo; Salman Khan (Molecular Biology Reports, 2026)

Synthesis, Characterization and Antibacterial Activity of DEAE-C Loaded Cefixime Nano-Particles Against Resistant Bacterial Strains - Muhammad Tayyub Kazam; Saman Arooj; Mahpara Tabassum; Hamid Saeed; Mehwish Iqtedar; Nadeem Ahmad; Muhammad Islam; Muhammad Fawad Rasool; Muhammad Usama; Aleena Maryam (Journal of Pharmaceutical Innovation, 2026)

Molecular target for neuroinflammation and pain management: transient receptor potential vanilloid 1 - Zunera Chauhdary; Muhammad Saad Masood; Muhammad Irfan; Amina Shafi; Duryab Rafique; Abeesha Arif; Maryam Akmal (Inflammopharmacology, 2026)

Exploring the epidemiology of Newcastle disease in Northern Nigeria: A mixed approach - Mayowa Peter Olabode; Usman Adamu Rayyanu; Victoria Isioma Ifende; Ismaila Shittu; Rebecca Paul Weka; Isabella Monne; Matthew Yakop Gukut; Ladi Amos Chabiri; Yakubu Joel Atuman; Judith Dizot Bakam; Falmata Haruna Bwala; Zenaba Mahamat Kodo; et al. (Preventive Veterinary Medicine, 2026)

Assessing the legacy effects of COVID-19 lockdowns on insect pollinator biodiversity - Muhammad Naeem; Ting Shen; Maryam Riasat; Nawaz Haider Bashir; Tahir Farooq; Zhumei Li; Huanhuan Chen; Canping Pan (Biological Conservation, 2026)

Transport of buoyant microplastics in natural soils under rainfall or irrigation conditions - Muhammad Masood Ashiq; Peyman Babakhani; Brian Waldron; Maryam Salehi; Kati Bell; Farhad Jazaei (ENGINEERING Environment, 2026)
Microplastics (MPs) pose a significant threat to soil and groundwater quality. Yet, investigating their transport in soils has so far been limited to conventional packed column experiments where particles suspended in a stock dispersion are injected from one side of the column. This, however, does not represent the natural condition where buoyant MPs are released on the surface of the soil and storm or irrigation water induces their penetration into the soil depth. To consider such prevailing natural condition, we develop a new column experiment setup and a corresponding modeling approach to study the transport of low-density polyethylene MPs in different farmland soil types and investigate the impact of photodegradation and natural organic matter. Results revealed a substantial penetration of buoyant MPs in the soil due to the irrigation or rainfall scenarios. Mathematical modeling showed that processes such as attachment, detachment, blocking, and straining, previously observed for colloidal particles in direct injection scenarios, occur for buoyant MPs irrigation or rainfall release scenario. MPs transport increased in silt compared to the silt loam and in the presence of natural organic matter. UV-photodegraded MPs transport was greater than pristine MPs because of increased surface charge and electrostatic repulsion, reducing MPs attachment to soil.

Chemical and Microbial Stabilization of Peat Soil Using Industrial Waste - Maryam Al Jaber; Nurmunira Muhammad; Ayah Almsedeen (Geotechnical and Geological Engineering, 2026)

Rebalancing α-Synuclein Clearance: Novel Therapeutic Frontiers in Parkinson’s Disease - Maryam Jabeen; Huma Hameed; Syed Muhammad Ahmad; Tehreem Mushtaq; Mahtab Ahmad Khan; Anam Hameed (NeuroMolecular Medicine, 2026)

Impact of green building features on perceived productivity and satisfaction in certified green office buildings in Klang Valley, Malaysia - Muhammad Tarique Lakhiar; Shalini Sanmargaraja; Maryam Kalhoro; AbdulLateef Olanrewaju; Chong Hooi Lim; Vignes Ponniah; Anselm Dass Mathalamuthu (Environment, Development and Sustainability, 2026)

Breakthrough advances in plant stress physiology: Acinetobacter schindleri SR-5–1 mitigates wastewater-induced nutrient imbalances in linseed plants - Sherjeel Hashmat; Umer Farooq; Muhammad Tariq Javed; Anni Maryam Afzal; Mohsin Raza Bukhari (Biologia, 2026)

Alleviation of salinity induced toxicity in quinoa (Chenopodium quinoa Willd.) through ascorbic acid application - Muhammad Faisal Maqsood; Tahira Fatima; Rehana Kanwal; Fozia Farhat; Muhammad Shahbaz; Muhammad Jamil; Saba Shafqat; Muhammad Asif; Muhammad Hamza Maqsood; Maryam Tariq; Usman Zulfiqar; Muhammad Ahmad (Biocatalysis and Agricultural Biotechnology, 2026)

Exploring ethyl methane sulphonate induced, L-cysteine HCl resistant Bacillus subtilis putative mutant and its immobilization for enhanced acetoin synthesis - Muhammad Usman Ahmad; Sikander Ali; Noor Ul Ain; Nabeera Shahzadi; Maryam Mustaid; Mahwish Arshad; Sadaf Ahmad; Bakar Bin Khatab Abbasi; Ali Irfan; Yousef A. Bin Jardan (Archives of Microbiology, 2026)

Helenalin: a multifaceted sesquiterpene lactone with diverse biological activities—an integrative pharmacological and computational evidence - Iqra Farzeen; Zunaira Jaan; Maryam Batool; Muhammad Muzammil Nazir; Derya Karatas Yeni; Muhammad Umar Ijaz; Asma Ashraf (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Evaluation of host suitability and larval instar effects on the reproductive potential of entomopathogenic nematodes against lepidopteran pests - Hina Safdar; Sumaira Maqsood; Salman Ghuffar; Aftab Ahmad; Muhammad Hafeez; Hifza Safdar; Tauseef Anwar; Huma Qureshi; Hossam S. El-Beltagi; Ibrokhim Ismoilov; Feruza Tukhtaboeva; Nazih Y. Rebouh; et al. (Crop Protection, 2026)

Assessment of Fine Particulate Matter (PM2.5) Induced Cyto-Genotoxicity in a Highly Polluted Urban Environment: Evidence from Lahore, Pakistan - Meerub Shazad; Muhammad Muddassir Ali; Syed Aziz ur Rehman; Maryam Javed; Jabir Hussain Syed; Asad Ullah (Water, Air, & Soil Pollution, 2026)

In vivo systemic toxicity assessment of Bacillus safensis NMCC-189: a probiotic strain evaluated via short-term tolerability and 28-day repeated-dose (OECD 407) study in Balb/c mice - Maryam Khan Sherwani; Syeda Rida Zainab; Jehan Zeb Khan; Shakira Ghazanfar; Fahim Hilal; Rimsha Noor; Muhammad Khalid Tipu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Correction: Molecular characterization and green synthesis of iron oxide nanoparticles from Ureibacillus chungkukjangi for methylene blue degradation - Muhammad Naveed; Muhammad Asim; Tariq Aziz; Shumaila Ibrahim; Maida Salah Ud Din; Maryam M. Alomran; Ashwag Shami; Fakhria A. Al-Joufi; Ahmad A. Alghamdi; Abdullah A. Alqasem; Ahmed M. Basri; Majid Alhomrani (Antonie van Leeuwenhoek, 2026)

Waste cooking oil conversion into multifunctional additives to develop economic bio-lubricant - Muhammad Sikandar; Javaria Ashiq; Ali Raza; Ameer Hamza; Mohammad Owais Aftab; Misbah Murshid; Maryam Rizwan; Azra Akbar; Muhammad Javid Iqbal (Sustainable Chemistry and Pharmacy, 2026)

Influence of Planting Depth Combined with ZnSO₄ and FeSO₄ on Yield and Starch Quality of Six Potato Cultivars - Harrem Khalid; Muhammad Shafiq; Muhammad Rizwan Tariq; Zain Mushtaq; Maryam Saeed (Potato Research, 2026)

Natural flavonoid isoorientin and its anticancer mechanisms: a systematic review - Muhammad Muzammil Nazir; Iqra Farzeen; Maryam Batool; Asma Ashraf (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Dental caries beyond eradication: microbiome centered and equilibrium driven therapeutic strategies - Maryam Jabeen; Huma Hameed; Areej Abdul Razzaq; Muhammad Jamshaid; Muhammad Amish Shakeel; Tehreem Mushtaq (Archives of Microbiology, 2026)

Ferruginol as multifunctional abietane diterpenoid-comprehensive pharmacological evaluation and computational drug discovery insight - Iqra Farzeen; Maryam Batool; Zunaira Jaan; Saira Saeed; Muhammad Muzammil Nazir; Shahla Faisal; Asma Ashraf (Phytochemistry Reviews, 2026)

Metabolic reprogramming of neurons in alzheimer disease: a biochemical perspective - Iqra Farzeen; Maryam Batool; Saira Saeed; Ghanva Mustafa; Munaza Yasmeen; Muhammad Muzammil Nazir; Asma Ashraf (Metabolic Brain Disease, 2026)

Green photocatalytic degradation of methylene green dye using oxalic acid and its metal complexes: Mechanistic and predictive insights from ANN, RSM, and DFT studies - Mohammad Tauseef Haider; Rizwan Ashraf; Talib H. Mawat; Faisal Jamil; Adnan Majeed; Anam Shahzadi; Faisal Qaleel; Haris Nadeem; Sabha Khalid; Asma Rehman; Sadia Aziz; Maryam Khalid; et al. (Journal of Water Process Engineering, 2026)

Alleviation of Lead Stress in Maize Plants Through the Application of Green-Synthesized Zinc Oxide Nanoparticles - Haseeba Maryam; Nasir Masood; Muhammad Waseem; Temoor Ahmed; Muhammad Zia-ur-Rehman; Muhammad Atif Irshad; Saher Javed; Muhammad Rizwan (Journal of Soil Science and Plant Nutrition, 2026)

Retraction notice to “Highly antifouling polymer-nanoparticle-nanoparticle/polymer hybrid membranes” [Sci. Total Environ. 810 (2022) / 152228] - Vahid Vatanpour; Maryam Jouyandeh; Seyed Soroush Mousavi Khadem; Shadi Paziresh; Ahmad Dehqan; Mohammad Reza Ganjali; Hiresh Moradi; Somayeh Mirsadeghi; Alireza Badiei; Muhammad Tajammal Munir; Ahmad Mohaddespour; Navid Rabiee; et al. (Science of The Total Environment, 2026)

Synergistic role of microbes and wetland plants in an advanced-acclimatized constructed wetland for enhanced removal of heavy metals - Adnan Abbas; Muhammad Ahmad; Maryam Yousaf; Linghui Pan; Dayong Xu (Gondwana Research, 2026)

Synergistic potential of clove oil and Bacillus culture filtrates (CFs) in suppressing the natural infection of Fusarium wilt pathogen in tomato - Muhammad Imran; Munirah F. Aldayel; Maryam M. Alomran; Reham A. Abd El Rahman; Kamal A. M. Abo-Elyousr; Muhammad Saqib Bilal; Zhongke Sun (Plant and Soil, 2026)

Drimiopsis maculata methanol extract attenuates inflammation in experimental rat model of polyarthritis: a biochemical and molecular insight - Malik Saadullah; Farwa Tahir; Maryam Farrukh; Samina Afzal; Rabia Munir; Usman Ashraf; Uzma Saleem; Muhammad Ajmal Shah; Ibrahim Aljaezi; Ana Sanchez Silva; Norah K. Algarzae; Musaad Bedah Alsahly (Inflammopharmacology, 2026)

Unveiling Hidden Threats: Molecular Detection and Genetic Diversity of Hepatozoon spp. and Toxoplasma Gondii in Wild Rodents of Saudi Arabia and Their Ectoparasites - Maryam Ijaz; Samia Q. Alghamdi; Abdullah D Alanazi; Mubashra Salim; Muhammad Naeem; Muhammad Ali; Shabana Mukhtiar; Kasim Sakran Abass; Hira Muqaddas; Adil Khan; Furhan Iqbal (Acta Parasitologica, 2026)

Development and validation of SR-DISVAXFIC: A mobile phone application for estimating the herd-level financial impact of small ruminant diseases and the potential benefits of vaccination in the field - Megan E. Rawlins; Adeyinka J. Adedeji; Victoria I. Ifende; Sandra I. Ijoma; Rebecca B. Atai; Joel Y. Atuman; Gambo Panzam; Haruna W. Gotom; Idris H. Adamu; Anas U. Musa; Isa M. Sani; Paul Adamu; et al. (Preventive Veterinary Medicine, 2026)

Green synthesis of biodiesel from novel non-edible Quercus baloot Griff seed oil catalyzed by iron-modified clay nanocatalyst - Maryam Naseem; Rozina; Okezie Emmanuel; Mushtaq Ahmad; Mehreen; Amjad Khan; Muhammad Zafar (Next Research, 2026)

Wheat-Berseem intercropping system enhances soil fertility, carbon sequestration and crop productivity under nutrient-deficient conditions - Zafar Iqbal; Sundas Bilal; Sana ur Rehman; Imran Haider; Maryam Saeed; Maqshoof Ahmad; Muhammad Ali Raza; Mehraj A. Abbasov; Walid Soufan (Plant and Soil, 2026)

Exploring smart solutions for stressed soils: dual-action of culture filtrates and nanoparticles for sustainable onion cultivation - Muhammad Imran; Maryam M. Alomran; Hanan A. Khalifa; Muhammad Saqib Bilal; Atef F. Ahmed; Esmat F. Ali; Abeer S. Alqurashi; Munirah F. Aldayel; Kamal A. M. Abo-Elyousr (European Journal of Plant Pathology, 2026)

Unravelling the Mechanistic Role of Soil Microbial Interactions in the Suppression of Phytopathogens in Vegetable Agroecosystems of Pakistan - Basit Khan; Nadeem Ullah; Haris Maqbool; Faria Khan; Izhar Khan; Afnan Khalid; Maryam Arshad; Najeeba Parre Paker; Iffat Naz; Muhammad Akmal; Muhammad Farooq Hussain Munis; Hassan Javed Chaudhary (Current Microbiology, 2026)

First-principles study on structural, elastic, acoustic and optoelectronic properties of hexagonal magnesium oxide (MgO) - Maryam Tariq; Tariq Mahmood; Robina Ashraf; Imran Aslam; Muhammad Rizwan; Arbab Arif; Ch. Omer Javed; Afshan Urooj (Next Research, 2025)

Innovative photothermal membrane distillation: Mitigating temperature polarisation with rice husk biochar - Chia Ming Liew; Mohd Hafiz Puteh; Mohd Hafiz Dzarfan Othman; Roziana Kamaludin; Siti Maryam Jasman; Parvin Asogan; Rendy Muhamad Iqbal; Mustapha Salisu Muhammad; Huda Nurul; Nor Ain Abu Samah; Jerry Heng; Huda Abdullah; et al. (Journal of Environmental Chemical Engineering, 2025)

Photo-mediated synthesis of Ag/ZnO Nanocomposite: A sustainable green approach for enhanced hydrogen production and photocatalytic degradation - Asif Khalil; Muhammad Zia Ur Rehman Faurooqi; Maryam Khalid; Tanveer Farid; Saghir Hussain; Khalid Mahmood (Fuel, 2025)

Comparative study on effect of Pleurotus florida treated and untreated wheat straw on feed intake, digestibility, and growth rate in cattle calves - Muhammad Tahir Khan; Haq Aman Ullah; Ihtisham Ul Haq; Maria Munir; Syeda Maryam Hussain; Muhammad Mushtaq; Nazir Ahmad Khan (Tropical Animal Health and Production, 2025)

Molecular Insights into Interactions between Ofloxacin and Ionic Micelles - Saqib Rabbani; Areesha Maryam; Muhammad Sohail; Athar Yaseen Khan (The Journal of Membrane Biology, 2025)

Morpho-Biochemical and SSR Marker-Based Genetic Diversity Assessment in Fig (Ficus carica) Genotypes - Muhammad Shahid Mumtaz; Muhammad Nafees; Ishtiaq Ahmad; Maryam; Adel A. Rezk; Jian Huang; Rashid Iqbal (Plant Molecular Biology Reporter, 2025)

Phenotypic Plasticity of Safflower Genotypes in Response to Contrasting Climatic Conditions - Obaid Afzal; Mukhtar Ahmed; Sahir Hameed Khattak; Muhammad Aqeel Aslam; Saida Komal; Maryam Murtaza; Farrukh Bashir; Aqeel Ahmad; Aliya Mirbaz; Haroon Ur Rasheed; Ghulam Muhammad Ali; Muhammad Usman; et al. (Plant Molecular Biology Reporter, 2025)

Rosa moschata leaf extract modulates complete freund’s adjuvant-induced polyarthritis in Wistar rats via regulation of pro-inflammatory and inflammatory biomarkers - Amr S. Abouzied; Uzma Saleem; Maryam Farrukh; Umme Farwa; Areej M. Alsolami; Fatima A. Jaber; Tourki A. S. Baokbah; Ibrahim Aljaezi; Nouf Abdullah Alharbi; Muhammad Ajmal Shah; Ana Sanchez Silva; Norah K. Algarzae (Inflammopharmacology, 2025)

When farmers’ knowledge matters: Improving epidemiological understanding of Peste des petits ruminants in northern Nigeria - Zenaba MAHAMAT KODO; Usman Adamu RAYYANU; Mayowa Peter OLABODE; Victoria Isioma IFENDE; Rebecca Paul WEKA; Matthew Yakop GUKUT; Alexis DELABOUGLISE; Ismaila SHITTU; Yakubu Joel ATUMAN; Judith Dizot BAKAM; Falmata Haruna BWALA; Ladi Amos CHABIRI; et al. (Preventive Veterinary Medicine, 2025)

Nonstationarity impacts on the assessment of drought conditions across diverse climate zones of Pakistan - Maryam; Rizwan Aziz; Ismail Yucel; Mahnoosh Moghaddasi; Muhammad Awais (Theoretical and Applied Climatology, 2025)

Pretreatment with probiotics (Bacillus safensis NMCC-189 and Bacillus clausii) prevents epileptogenesis in mice via modulation of BBB integrity, oxidative stress, and neurotransmitter balance - Maryam Khan Sherwani; Jehan Zeb Khan; Shakira Ghazanfar; Fahim Hilal; Rimsha Noor; Muhammad Khalid Tipu (Inflammopharmacology, 2025)

A machine learning assisted approach to classify rose species and varieties with laser induced breakdown spectroscopy - Maryam Manzoor; Muhammad Faheem; Muhammad Nadeem; Guljan Shreen; Faisal Hayat; Adnan Younis; Yasir Jamil (Analytica Chimica Acta, 2025)

The impact of Rhizobacteria and micronutrients on fitness parameters and oxidative stress of predatory ladybird, Adalia bipunctata (Coleoptera: Coccinellidae) - Maryam Pourya; Jahanshir Shakarami; Mozhgan Mardani-Talaee; Amin Sadeghi; Muhammad Z. Ahmed (Applied Entomology and Zoology, 2025)
The predatory ladybird, Adalia bipunctata (Linnaeus) (Coleoptera: Coccinellidae), is a polyphagous species that primarily feeds on aphids. In this study, we assessed the demographic parameters and antioxidant activities of A. bipunctata individuals that were fed on Sitobion avenae (Fabricius) (Hemiptera: Aphididae) reared on wheat treated with Plant Growth-Promoting Rhizobacteria (PGPRs) (Biofarm and Probio96) and micronutrients (Librel Zinc and Alpha-Iron). The results showed that the shortest preadult period of A. bipunctata was recorded for individuals reared under Probio96 and Biofarm treatments. Additionally, the highest values of intrinsic rate ( r ) and net reproductive rate ( R 0 ) of the predator were recorded under the Probio96 treatment, while the lowest values were observed with Alpha-Iron. The lowest activity levels of catalase, oxidized/reduced thiols ratio, peroxidase, and superoxide dismutase were found in 4th instar larvae. In contrast, the lowest antioxidant activities, except ascorbate peroxidase, were observed in adults. These findings were attributed to aphids reared on wheat fertilized with Probio96. It can be concluded that combining host plant resistance with Plant Growth-Promoting Rhizobacteria and biological control may offer an effective strategy for the integrated management of aphids.

Pinobanksin ameliorates perfluorooctane sulfonate-evoked cardiotoxicity via targeting Nrf-2/Keap-1, oxidative damage and inflammation in Sprague Dawley rats - Maryam Javed; Quratulann Sattar; Muhammad Faisal Hayat; Hamida Hamdi; Muhammad Zaid Salar (Tissue and Cell, 2025)

Multicriteria evaluation of cropland suitability using multisource datasets of satellite remote sensing and ground observation - Danish Raza; Hong Shu; Sahar Mirza; Hasnat Aslam; Aqil Tariq; Rana Waqar Aslam; Hafsa Aeman; Muhsan Ehsan; Maryam Muhammad Ali (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Waste to wonder: Sustainable photocatalytic biochar from agro-plastic waste for advanced wastewater treatment - Muhammad Ahmad; Maryam Yousaf (Journal of Environmental Chemical Engineering, 2025)

Restoration of alkaline soils contaminated by inorganic elements under pulsed electrokinetics - Abdul Ahad Hussain; Muhammad Moeez; Aasma Akram; Mubashera Ishaq; Kashif Kamran; Muhammad Afzaal; Maryam Hina; Lin Li (Environmental Research, 2025)

AI-powered optimization of reactive red 195 dye decolorization: Evaluating the impact of operational factors - Zubair Khaliq; Anum Javaid; Abdulaziz Bentalib; Muhammad Bilal Qadir; Zubera Naseem; Shumaila Kiran; Fayyaz Ahmad; Nimra Nadeem; Maryam Bibi (Desalination, 2025)

Heat Tolerance in Omani Lentil Landraces and Their Stress Responses to Elevated Temperatures - Maryam Ismail Al Zeidi; Muhammad Farooq (Journal of Plant Growth Regulation, 2025)

Target Mining in Insect Genomes: Omics-Guided Innovations for Smart Pesticides - Muhammad Faizan Khurram; Maryam Tahira; Abdul Rauf; Burhan Khalid; Muhammad Ikram (Journal of Crop Health, 2025)

Correction: Ipomoea carnea Jacq. ameliorates formalin-induced paw inflammation in rats through modulation of oxidative and inflammatory pathways - Shabab Nasir; Muhammad Usman; Humaira Gul; Malik Saadullah; Maryam Farrukh; Rida Siddique; Bushra Shaukat; Abdullah R. Alanzi; Ana Sanches Silva; Muhammad Ajmal Shah (Inflammopharmacology, 2025)

Effect of pollen sources on biochemical indices and hybrid authentication in date palm (Phoenix dactylifera L.) cv. Khadrawy - Maryam; Ishtiaq Ahmad; Muhammad Nafees; Muhammad Saqib; Mona S. Alwhibi; Mohamed S. Elshikh; Mehmet Ramazan Bozhuyuk; Javed Iqbal; Shabir Ahmad; Trobjon Makhkamov; Ghulam Murtaza; Rashid Iqbal (Genetic Resources and Crop Evolution, 2025)

Molecular characterization and green synthesis of iron oxide nanoparticles from Ureibacillus chungkukjangi for methylene blue degradation - Muhammad Naveed; Muhammad Asim; Tariq Aziz; Shumaila Ibrahim; Maida Salah Ud Din; Maryam M. Alomran; Ashwag Shami; Fakhria A. Al-Joufi; Ahmad A. Alghamdi; Abdullah A. Alqasem; Ahmed M. Basri; Majid Alhomrani (Antonie van Leeuwenhoek, 2025)

Blue carbon management integrating socioeconomic and environmental interconnectivity in Southeast Asia: an urgent climate priority - Amani Becker; Sarah K. Bercovici; Jenny Choo; Fakhrurrozi Fakhrurrozi; Annabelle Fong; Sara E. Fowell; Emmy Hossain; Muhammad Ali Syed Hussein; Maryam Jamilah; Aazani Mujahid; Moritz Müller; Jillian Lean Sim Ooi; et al. (Frontiers in Marine Science, 2025)
This perspective article synthesises insights from a 2023 interdisciplinary workshop in Kuching, Malaysia, where 26 experts examined how land use and land cover change (LULCC) impacts Blue Carbon Ecosystems (BCE) in Southeast Asia (SEA) and identified pathways for integrated, science-informed governance. BCE in SEA (mangroves, seagrasses and tidal wetlands) are globally significant carbon sinks, critical to biodiversity and the livelihoods of millions, dependant on them for food, income and coastal protection. Yet rapid development and socio-economically driven LULCC threaten BCE resilience and carbon storage capacity. Blue Carbon initiatives risk falling short if they overlook the socio-ecological interconnectivity of these systems. Advances in remote sensing, sediment carbon accounting and ecosystem modelling have improved BCE monitoring, but key gaps persist. These include understanding cumulative upstream effects of LULCC on BCE carbon dynamics, integrating socio-economic with ecological data for robust scenario modelling and evaluating governance effectiveness and equity over time. We frame BCE as dynamic, interconnected socio-ecological systems and call for the advancement of systems thinking in coastal and climate policy. We underscore the need for transdisciplinary, nested governance models operating across ecological scales and political boundaries and argue for a systems-based management approach that links land-sea processes, addresses upstream-downstream dynamics and balances carbon market incentives with local needs. Recommendations include improved monitoring and carbon accounting; alignment between science and policy; regionally coordinated governance; and diversifying finance to reflect the full value of BCE beyond carbon. Together, these actions chart a path for resilient, science-based, socially inclusive BCE conservation in SEA.

Recent advances in beta-type hexagonal ferrites: Synthesis, structural, vibrational and electromagnetic characteristics - M. Irfan; Shafaq Waqar; Hafiz Ghulam Shabbir; Tehreem Idrees; Fatima Khan; Komel Maryam; Maryam Choudhary; Isbah Shamshad; Abdul Rehman Ashiq; Shagufta Gulbadan; Muhammad Azhar Khan; Nayyab Sajjad (Next Research, 2025)

Corrigendum to “AI-powered optimization of reactive red 195 dye decolorization: Evaluating the impact of operational factors” [Desal. Volume 612 (2025), article number: 118936 https://doi.org/10.1016/j.desal.2025.118936] - Zubair Khaliq; Anum Javaid; Abdulaziz Bentalib; Muhammad Bilal Qadir; Zubera Naseem; Shumaila Kiran; Fayyaz Ahmad; Nimra Nadeem; Maryam Bibi (Desalination, 2025)

Enhanced you only look once v5s crack detection and classification technique by optimizing transformer architecture and convolutional complexity - Umar Ali; Muhammad Arshad Shehzad Hassan; Asim Khan; Muhammad Zeeshan Khan; Maryam Shahzadi (Innovative Infrastructure Solutions, 2025)

The carcinogenic risks of military explosives: mechanisms, health impacts, and environmental consequences of chemical munitions - Madinat Hassan; Taofeek Tope Adegboyega; Sunday Zeal Bala; Jemila Saleh; Muhibat Bolanle Komolafe; Maryam Yahaya Muhammad; Daniel Danladi Gaiya; Amina Shehu Bature; Miracle Uwa Livinus (Toxicology and Environmental Health Sciences, 2025)

Functionalized carbon nanotubes interconnected with metal-organic frameworks for in-situ solar-driven evaporation and salt recovery from seawater - Muhammad Sohail Asghar; Muhammad Sultan Irshad; Naila Arshad; Maryam Al Huwayz; Muneerah Alomar; Ghazala Maqsood; Muhammad Atif Ali; Uzma Ghanzanfar; Muhammad Sabir; Jinhua Li; Van-Duong Dao; Nang Xuan Ho; et al. (Water Research, 2025)

Molecular detection, epidemiology and phylogenetic evaluation of Babesia ovis in apparently healthy goats - Asia Taqddus; Muhammad Naeem; Hira Muqaddas; Ceylan Ceylan; Onur Ceylan; Ferda Sevinc; Maryam Rahravani; Meysam Moravedji; Alireza Sazmand; Furhan Iqbal (Research in Veterinary Science, 2025)

An integrated evaluation framework for evaluating renewable-based building sector implementation in remote/off-grid areas with varying climatic zones - Rida Maryam; Syed Ali Abbas Kazmi; Muhammad Hassan; Mustafa Anwar (Energy and Buildings, 2025)

Development of a Novel Multi-Model Ensemble Weighting Scheme for Improved Drought Assessment - Mahrukh Yousaf; Ali Iqbal; Sadia Qamar; Muhammad Shakeel; Maryam Ilyas; Zulfiqar Ali; Rizwan Niaz (Water Conservation Science and Engineering, 2025)

Review on crack detection in civil infrastructure using structural health monitoring and machine learning techniques - Muhammad Zeeshan Khan; Maryam Shahzadi; Asim Khan; Umar Ali; Muhammad Arshad Shehzad Hassan; Majid Hussain (Innovative Infrastructure Solutions, 2025)

Cyto-genotoxic assessment of bisphenol P through expression of DNA damage/repair genes in MDBK cell line - Muhammad Muddassir Ali; Samra Afzal; Maryam Javed; Imran Rashid; Furqan Awan; Asad Ullah; Tanveer Majeed; Hadeer Darwish; Ahmed Noureldeen; Jawaher Albaqami; Khalid Mehmood (In Vitro Cellular & Developmental Biology - Animal, 2025)

Co-conversion of CO2 and refractory organics into bioplastics through a stable biocarrier - Muhammad Ahmad; Maryam Yousaf (Water Research, 2025)

7β-(3-ethyl-cis-crotonoyloxy)-1α-(2-methylbutyryloxy)-3,14-dehydro-Z-notonipetranone (ECN) attenuates inflammation and oxidative stress via MAPK, and Nrf2/HO-1 signaling in Traumatic brain injury - Sana Zafar; Maryam Jamil; Muhammad Ibrar Khan; Fakhar ud Din; Eun Kyoung Seo; Salman Khan (Chemico-Biological Interactions, 2025)

Critical appraisal of “altered white matter architecture in patients with isolated congenital anosmia” - Muhammad Taaha Siddiqui; Nawal Fatima; Eman Fatima; Maryam Amjad; Mahnoor Khan (Brain Structure and Function, 2025)

Machine learning-based detection and quantification of red blood cells in Cholistani cattle: A pilot study - Sami Ul Rehman; Sania Fayyaz; Muhammad Usman; Mehreen Saleem; Umer Farooq; Asjad Amin; Mushtaq Hussain Lashari; Musadiq Idris; Haroon Rashid; Maryam Chaudhary (Research in Veterinary Science, 2025)

Effect of Microplastic Contamination and Bradyrhizobium japonicum Inoculation on Glycine max Growth and Soil Bacterial Community - Maryam Abdulazeez Hassan; Muhammad Bashir Tijjani; Seniyat Larai Afegbua (Water, Air, & Soil Pollution, 2025)

Ipomoea carnea Jacq. ameliorates formalin-induced paw inflammation in rats through modulation of oxidative and inflammatory pathways - Shabab Nasir; Muhammad Usman; Humaira Gul; Malik Saadullah; Maryam Farrukh; Rida Siddique; Bushra Shaukat; Abdullah R. Alanzi; Ana Sanches Silva; Muhammad Ajmal Shah (Inflammopharmacology, 2025)

N-Dimethyl chalcone facilitated augmentation of IL-10 and diminution of TNF-α, IL-1β, IL-6, NFκB, and COX-2 in FCA-induced arthritic rat model - Faiza Waseem; Ali Sharif; Maryam Shabbir; Bushra Akhtar; Syed Wadood Ali Shah; Shahnaz; Adeel Arshad; Ejaz Basheer; Muhammad Asif Hanif; Muhammad Ali (Inflammopharmacology, 2025)

Molecular and functional analysis of a putative pyocin S9, with endonuclease activity from P. chlororaphis subsp aurantiaca PB-St2 - Maryam Zareen; Deeba Noreen Baig; Muhammad Imran; Zabish Khaliq; Kausar Abdulla Malik; Andreas Bechthold; Samina Mehnaz (Archives of Microbiology, 2025)

Harvest Time Influences Quality and Storability of ‘Chandler’ Strawberries Grown Under Subtropical Conditions of Pakistan - Ayesha Maryam; Raheel Anwar; Mahmood Ul Hasan; Sajid Ali; Ahmad Sattar Khan; Muhammad Moaaz Ali; Khurram Ziaf (Applied Fruit Science, 2025)

Role of polyphenolics in the management of rheumatoid arthritis through intracellular signaling pathways: a mechanistic review - Uzma Saleem; Maryam Farrukh; Malik Saadullah; Rida Siddique; Humaira Gul; Aqsa Ahmad; Bushra Shaukat; Muhammad Ajmal Shah (Inflammopharmacology, 2025)

Rhizospheric bacterial strain Pseudomonas putida and fungal strain Penicillium chrysogenum alleviate Fusarium wilt of tomato by improving key growth attributes - Hassaan Ateeb Ahmad; LNU Farhana; Urooj Haroon; Hira Saleem; Maryam Anar; Mahnoor Akbar; Kanwal Abbasi; Abdul Rehman; Mohammad Sameer Zubair; Asif Kamal; Hassan Javed Chaudhary; Rattandeep Singh; et al. (European Journal of Plant Pathology, 2025)

Enhancing defense and production efficiency in rainbow trout (Oncorhynchus mykiss) through prophylactic dietary selenium and vitamin E fortification - Said Jasim Shah; Noor Khan; Mahroze Fatima; Sheeza Bano; Ayesha Tanveer; Sadia Nazir; Muhammad Asghar; Ahmed Mustafa; Maryam Tahir; Saba Aftab; Alex Hing Leung Wan; Simon John Davies (Animal Feed Science and Technology, 2025)

Biocompatible Nitro Group-Based Photosensitizer for AIE, Hypoxia, and Photodynamic Therapy. Experimental and Theoretical Approach - Maryam Rana; Munaza Pervaiz; Muhammad Arif Ali; Muhammad Ahmad; Laiqi Zhang; Shengnan Yin; Tansir Ahamad; Mansoor Akhtar (Journal of Fluorescence, 2025)

Text clustering with a hybrid multi-objective optimization approach: The multi-objective firefly differential Jaya Algorithm - Muhammad Naderi; Maryam Amiri (Swarm and Evolutionary Computation, 2025)

Biocatalytic application of chitosan-silver nanocomposite (Ch-AgNP) to reduce vascular colonization and induce wilt resistance in Brassica napus L. against both Fusarium oxysporum and Verticillium dahliae - Rabia Nawab; Mahnoor Akbar; Maryam Anar; Hassan Javed Chaudhary; Muhammad Farooq Hussain Munis (Physiological and Molecular Plant Pathology, 2025)

Correction: Salt Tolerance in Omani Lentil Landraces: Impacts on Growth, Root Architecture, Ion Homeostasis, Proline Accumulation, and Antioxidant Defence System - Maryam I. Al-Zeidi; Mahmoud W. Yaish; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2025)

Salt Tolerance in Omani Lentil Landraces: Impacts on Growth, Root Architecture, Ion Homeostasis, Proline Accumulation, and Antioxidant Defence System - Maryam I. Al-Zeidi; Mahmoud W. Yaish; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2025)

Theabrownin: a dietary nutraceutical with diverse anticancer mechanisms - Muhammad Faisal Maqbool; Sameena Gul; Muhammad Ishaq; Amara Maryam; Muhammad Khan; Hafiz Abdullah Shakir; Muhammad Irfan; Yongming Li; Tonghui Ma (Natural Product Research, 2025)

Heavy metals pollution in riverine sediments: Distribution, source, and environmental implications - Kifayatullah Khan; Muhammad Younas; Muhammad Yaseen; Hassan Sher; Afsheen Maryam; Sobhy M. Ibrahim; Adnan Adnan; Ahmad Ali; Muhammad Fawad; Akhtar Zeb Khan; Nasrullah Khan; Izaz Ali Shah (Environmental Monitoring and Assessment, 2025)

Pathways and risk analysis of arsenic and heavy metal pollution in riverine water: Application of multivariate statistics and USEPA-recommended risk assessment models - Kifayatullah Khan; Muhammad Sajawal Khan; Muhammad Younas; Muhammad Yaseen; Abdullah G. Al-Sehemi; Yasar N. Kavil; Chao Su; Niaz Ali; Afsheen Maryam; Ruoyu Liang (Journal of Contaminant Hydrology, 2025)

Tailoring the electrochemical performance of rods-like Co-MOF: Fe-derived Co3O4: Fe electrodes for supercapacitor applications - Maryam Shah; Sonadia; Zoya Iqbal; Anwar Ul-Hamid; Muhammad Umair Mushtaq; Fahad Azad (Fuel, 2025)

First report of Hepatozoon and Lankesterella spp. infections in wild rodents from Pakistan, and their potential impact on blood parameters and oxidative stress markers in vital organs - Maryam Ijaz; Asmat Ullah Khan; Muhammad Ali; Shakir Ullah; Muhammad Naeem; Samir Ibenmoussa; Turki M. Dawoud; Adil Khan; Mourad Ben Said; Furhan Iqbal (Veterinary Research Communications, 2025)

Multi-scale computational modeling to identify novel chemical scaffolds as trehalose-6-phosphate phosphatase inhibitors to combat Burkholderia pseudomallei - Sara Noor; Mohammad Abdullah Aljasir; Maryam Bashir; Kalsoom Khan; Sajjad Ahmad; Syed Ainul Abideen; Saifullah Khan; Farhan Siddique; Hamza Ahmad; Khudija Ghani; Madiha Iqbal; Muhammad Irfan; et al. (In Silico Pharmacology, 2025)

Palyno-anatomical diversity and its implication in the taxonomy of some Plantaginaceae species - Maryam Akram Butt; Nafeesa Zahid; Saraj Bahadur; Sadaf Kayani; Javeed Hussain; Muhammad Zafar (Genetic Resources and Crop Evolution, 2025)

Human Brucellosis in the Rural and Urban Population of Pakistan: Seroprevalence, Risk Factors, and Clinical Manifestations - Faisal Abbas; Shahzad Ali; Ali Muhammad; Asima Azam; Amira A. Moawad; Mohammad Ejaz; Anam Iftikhar; Maryam Dadar (Current Microbiology, 2025)

Nutraceutical Impact of Pumpkin Seed Oil on Expression Levels of EZH-2 and KRT-14 Genes against DSS-induced Inflammatory Bowel Disease in the Rat Model - Asma Mukhtar; Imran Mukhtar; Humaira Muzaffar; Muhammad Naeem Faisal; Kashif ur rehman khan; Laaraib Nawaz; Muhammad Umar Ijaz; Sana Maryam; Muhammad Umair; Haseeb Anwar; Farid S. Ataya; Gaber El-Saber Batiha; et al. (Cell Biochemistry and Biophysics, 2025)
Inflammatory bowel disease is a collection of intestinal disorders that cause inflammation in the digestive tract. Prolonged inflammation in the gastrointestinal tract is a major risk factor for colorectal cancer. The objective of this study was to fucus on gene expression levels of ( KRT-14 ; associated with epithelial cell integrity) and enhancer of zeste homolog-1 ( EZH-2; involved in cellular proliferation) in a IBD rat model in order to rule out impact of nutraceuticals (pumpkin seed oil; PSO) as a complementary approach to conventional treatments of IBD. In the current study, IBD was induced using dextran sodium sulfate (DSS). Following acclimatization, rats were separated into three groups: the negative control, the positive control, and the treatment group. The DSS (1 ml/kg bw) was given to the positive control and treatment groups. Negative control was given only a normal diet. Pumpkin seed oil (PSO) was given orally as a treatment (0.5 ml/kg bw). Blood and colon tissue were obtained on the 5 th , 10 th , 14 th, and 18 th days. Physical parameters, hematology, biochemical assays, gene expression, and histopathology were carried out. After statistical analyses, macroscopic parameters showed significant differences. Biochemical analyses revealed a significant ( P ≤ 0.05) decrease in serum potassium concentrations, total cholesterol, triglycerides, total proteins, total oxidants status, and C-reactive proteins in PSO treated group as compared with positive control. Gene expression levels of KRT-14 and EZH2 were significantly ( P ≤ 0.05) upregulated in PSO treated group as compared to positive control group. Histopathology revealed that pumpkin seed oil preserved the structural integrity of colon.

Zinc-lysine and iron-lysine mitigate chromium toxicity in pearl millet (Pennisetum glaucum) through modulating photosynthetic and antioxidant system and inhibiting chromium uptake and translocation - Zaryab Ali Abbass; Maryam Zahra; Habib Ali; Muhammad Javed; Imran Mahmood; Mavadat Hussain Alvi; Alishba Waheed; Sadam Hussain; Sachin Kumar (Environmental Science and Pollution Research, 2024)

Mitigating lead (Pb) toxicity in Zea mays (L.) plants using green synthesized iron oxide nanoparticles - Haseeba Maryam; Muhammad Rizwan; Nasir Masood; Muhammad Waseem; Temoor Ahmed; Muhammad Farooq Qayyum; Muhammad Zia-ur-Rehman; Humera Aziz (South African Journal of Botany, 2024)

Potential of iron oxide-modified biochar in simultaneous mitigation of lead and nickel toxicity in wheat (Triticum aestivum L.) - Tufail Shah; Muhammad Kashif Irshad; Wasim Javed; Mahshab Sheraz; Atif Muhmood; Ali Noman; Maryam M. Alomran; Sang Soo Lee; Jianying Shang (South African Journal of Botany, 2024)

Multilayered photo-bioanode for simultaneous conversion of CO2 and industrial refractory organics into bioelectricity in a microbial fuel cell system - Muhammad Ahmad; Maryam Yousaf; Aisha Batool; Hafiz Muhammad Adeel Sharif (Fuel, 2024)

Molecular epidemiology of brucellosis in Asia: insights from genotyping analyses - Shahzad Ali; Areeba Mushtaq; Laiba Hassan; Muhammad Ali Syed; Jeffrey T. Foster; Maryam Dadar (Veterinary Research Communications, 2024)

Association of polymorphism of NLRP3, ICAM-1, PTPN22, INS genes in childhood onset type 1 diabetes in a Pakistani population - Anjum Jabeen; Samreen Riaz; Muhammad Usman; Asia Parveen; Maryam Mukhtar; Abdul Wajid; Atif Hanif; Andleeb Batool (Molecular Biology Reports, 2024)

Zebrafish as an innovative model for exploring cardiovascular disease induction mechanisms and novel therapeutic interventions: a molecular insight - Shaukat Ali; Maryam Zulfiqar; Muhammad Summer; Mahnoor Arshad; Shehzeen Noor; Laiba Nazakat; Abdullah Javed (Molecular Biology Reports, 2024)

CRISPR-Cas9 based molecular breeding in crop plants: a review - Muhammad Ikram; Abdul Rauf; Muhammad Junaid Rao; Muhammad Faizan Khurram Maqsood; Muhammad Zeeshan Mola Bakhsh; Maaz Ullah; Maria Batool; Muhammad Mehran; Maryam Tahira (Molecular Biology Reports, 2024)

Combinatorial targeting of telomerase and DNA-PK induces synergistic apoptotic effects against Pre-B acute lymphoblastic leukemia cells - Maryam Katoueezadeh; Parisa Maleki; Seyedeh Atekeh Torabizadeh; Alireza Farsinejad; Roohollah Mirzaee Khalilabadi; Hajar Mardani Valandani; Ismaila Olanrewaju Nurain; Muhammad Hossein Ashoub; Ahmad Fatemi (Molecular Biology Reports, 2024)

Correction: Examining Adaptive Responses of Foeniculum vulgare to Elevated Sodium and Chloride Stress in the Root Zone - Noreen Akhter; Rimsha Nafees; Ali Noman; Muhammad Aqeel; Naila Hadayat; Noreen Khalid; Abida Kausar; Mohammed O. Alshaharni; Muhammad Muslim Shahnaz; Arsal Saleem; Maryam M. Alomran (Journal of Soil Science and Plant Nutrition, 2024)

Examining Adaptive Responses of Foeniculum vulgare to Elevated Sodium and Chloride Stress in the Root Zone - Noreen Akhter; Rimsha Nafees; Ali Noman; Muhammad Aqeel; Naila Hadayat; Noreen Khalid; Abida Kausar; Mohammed O. Alshaharni; Muhammad Muslim Shahnaz; Arsal Saleem; Maryam M. Alomran (Journal of Soil Science and Plant Nutrition, 2024)

Sedimentology, diagenesis and sequence stratigraphy of the Early–Middle Eocene Chorgali Formation in the Hazara sub-Basin, Northwest Himalayas, Pakistan - Emad Ullah Khan; Shadab Khan; Syed Muhammad Wasim Sajjad; Maryam Saleem; Muhammad Ilyas; Saif Ullah Khan (Carbonates and Evaporites, 2024)

Leading report regarding the molecular epidemiology of Taenia hydatigena from Pakistan and global overview of the genetic diversity and population structure of the parasite - Naunain Mehmood; Hira Muqaddas; Aqsa Ashraf; Mahnoor Aslam; Maryam Khan; Madiha Fatima; Rahman Qadir; Samir Ibenmoussa; Turki M. Dawoud; Muhammad Irfan Ullah; Furhan Iqbal (Comparative Immunology, Microbiology and Infectious Diseases, 2024)

Comprehensive assessment of heavy metal contamination in soil-plant systems and health risks from wastewater-irrigated vegetables - Muhammad Anis Aslam; Muhammad Sohail Abbas; Muhammad Mustaqeem; Maryam Bashir; Adeeba Shabbir; Muhammad Talha Saeed; Rana Muhammad Irfan (Colloids and Surfaces C: Environmental Aspects, 2024)

Proximate composition and prevalence and exposure assessment of aflatoxins intake through consumption of fresh carrot and processed marketed carrot products in South Punjab, Pakistan - Aneela Nijabat; Shahwana Bibi; Maryam Ajmal; Saher Nawaz; Muhammad Zaheer Sajid; Saad Ullah Khan Leghari; Muhammad Mahmood-ur-Rehman; Naima Huma Naveed; Aamir Ali; Philipp W. Simon (Natural Product Research, 2024)

Synthesis, Crystal Structure and Fluorimetric Study of 2-phenylphthalazin-1(2H)-one: a Highly Selective Florescent Chemosensor for Detection of Fe3+ and Fe2+ Metal Ions - Shahzad Sharif; Muhammad Shahbaz; Onur Şahin; Muhammad Aqib Khurshid; Maryam Musaffa Anbar; Birra Dar (Journal of Fluorescence, 2024)

Integrative multi-target analysis of Urtica dioica for gout arthritis treatment: a network pharmacology and clustering approach - Maryam Qasmi; Muhammad Mazhar Fareed; Haider Ali; Zarmina Khan; Sergey Shityakov (In Silico Pharmacology, 2024)

Photocatalytically active layered double hydroxide-PVDF composite membranes for effective remediation of dyes contaminated water - Mukarram Zubair; Muhammad Yasir; Michal Machovsky; Nadeem Baig; Mohammad Saood Manzar; Jehad Abdulfatah Sadeq Odeh; Mohamed K. Hassan; Alaa Hawari; Jehad Odeh; Emre Cevik; Maryam Al-Ejji (Chemosphere, 2024)

Biogenic iron oxide nanoparticles (Fe2O3 NPs) adeptly diminish leaf blight of Rosa chinensis by exhibiting higher expression of RcWRKY29 and increasing antioxidant enzymatic activities - Hira Saleem; Mahnoor Akbar; Maryam Anar; Hassan Javed Chaudhary; Muhammad Farooq Hussain Munis (South African Journal of Botany, 2024)

Plant growth promoting Dictyosphaerium DHM2 derived magnesium peroxide nanoparticles with antibacterial, antioxidant and photocatalytic properties - Kausar Chaudhary; Shafia Maryam; Sajid Iqbal; Abdullah Ahmad; Muhammad Tahir; Hussnain Ahmed Janjua (Algal Research, 2024)

Bacteria-Based MnO Nanoparticles Alleviate Lead Toxicity in Tomato Seedling Through Improving Growth Attributes and Enhanced Gene Expression of Candidate Genes - Maryam Anar; Urooj Haroon; Asif Kamal; Kinza Tahir; Mahnoor Akbar; Farhana; Hira Saleem; Abdul Rehman; Hassan Javed Chaudhary; Muhammad Farooq Hussain Munis (Journal of Plant Growth Regulation, 2024)

Population exposure to emerging perfluoroalkyl acids (PFAAs) via drinking water resources: Application of multivariate statistics and risk assessment models - Kifayatullah Khan; Muhammad Younas; Jafar Ali; Noor Samad Shah; Yasar N. Kavil; Mohammed A. Assiri; Xianghui Cao; Hassan Sher; Afsheen Maryam; Yunqiao Zhou; Muhammad Yaseen; Li Xu (Marine Pollution Bulletin, 2024)

Florfenicol removal from veterinary pharmaceutical effluents: Tri-metallic zeolite 5A° for electrochemical oxidation and catalytic ceramic membrane separation - Amir Ikhlaq; Maryam Gull; Afnan Sajid; Khurram Saleem Joya; Muhammad Raashid; Osama Shaheen Rizvi; Zafar Masood; Salman Ahmed; Maryam Abid; Maham Hanif; Hafiz Abdul Aziz; Thamer Abdulhameed Al Johani; et al. (Journal of Environmental Chemical Engineering, 2024)

Microbial goldmine: Investigating probiotic floral diversity in human breast milk - Ayesha Saeed; Azra Yasmin; Mehreen Baig; Maryam Pervaiz; Muhammad Arslan Ahmed; Muhammad Tabish; Humaira Hashmat (Bioactive Carbohydrates and Dietary Fibre, 2024)

Preparation and characterization of green silicon nanoparticles and their effects on growth and lead (Pb) accumulation in maize (Zea mays L.) - Haseeba Maryam; Ghulam Hassan Abbasi; Muhammad Waseem; Temoor Ahmed; Muhammad Rizwan (Environmental Pollution, 2024)

Recent advances in nanocellulose-based two-dimensional nanostructured membranes for sustainable water purification: A review - Mukarram Zubair; Muhammad Yasir; Deepalekshmi Ponnamma; Hassam Mazhar; Vladimir Sedlarik; Alaa H. Hawari; Mamdouh Ahmed Al-Harthi; Maryam Al-Ejji (Carbohydrate Polymers, 2024)

Bacillus safensis filtrate-based ZnO nanoparticles control black heart rot disease of apricot fruits by maintaining its soluble sugars and carotenoids - Farhana; Abu Bakr Umer Farooq; Urooj Haroon; Hira Saleem; Mahnoor Akbar; Maryam Anar; Muhammad Nawaz; Hassaan Ateeb Ahmad; Junaid Ahmed; Hassan Javed Chaudhary; Muhammad Farooq Hussain Munis (World Journal of Microbiology and Biotechnology, 2024)

Molecular prevalence of vector borne bacterial pathogens in the blood samples of wild rodent species trapped from Saudi Arabia - Abdul Ghafar; Samia Q. Alghamdi; Abdullah D. Alanazi; Syed Muhammad Zukhruf Qousain; Maryam Ijaz; Muhammad Naeem; Muhammad Ali; Hira Muqaddas; Adil Khan; Furhan Iqbal (Comparative Immunology, Microbiology and Infectious Diseases, 2024)

Harnessing Melatonin Protective Efficacy in Capsicum Plants Against Nickel-Contaminated Soil - Maryam M. Alomran; Ali Noman; Noreen Khalid; Naila Hadayat; Fatmah M. Alqahtani; Fahad Mohammed Alzuaibr; Noreen Akhter; Mohamed Hashem; Talaat Habeeb; Omar Mahmoud Al-Zoubi; Muhammad Aqeel (Journal of Soil Science and Plant Nutrition, 2024)

Efficient performance of InP and InP/ZnS quantum dots for photocatalytic degradation of toxic aquatic pollutants - Maryam Abbasi; Rukhsanda Aziz; Muhammad Tariq Rafiq; Aziz Ur Rahim Bacha; Zahid Ullah; Abdul Ghaffar; Ghulam Mustafa; Iqra Nabi; Malik Tahir Hayat (Environmental Science and Pollution Research, 2024)

Investigating biodiesel production from Chicken fat oil using bi-functional catalysts and microbubble mediated mass transfer - Maryam Asif; Fahad Javed; Muhammad Younas; Mazhar Amjad Gillani; William B. Zimmerman; Fahad Rehman (Fuel, 2024)

Extracellular microvesicles: biologic properties, biogenesis, and applications in leukemia - Muhammad Hossein Ashoub; Maryam Samareh Salavatipour; Fatemeh Hoseinpour Kasgari; Hajar Mardani Valandani; Roohollah Mirzaee Khalilabadi (Molecular and Cellular Biochemistry, 2024)

Effect of experimental boundary conditions and treatment-time on the electro-desalination of soils - Abdul Ahad Hussain; Kashif Kamran; Muhammad Imran; Aasma Akram; Lin Li; Maryam Hina; Muhammad Yasin Naz; Muhammad Shabir Mahr; Athar Mahmood; Abdallah A. A. Mohammed (Environmental Geochemistry and Health, 2024)

Cassia Angustifolia Primed ASCs Accelerate Burn Wound Healing by Modulation of Inflammatory Response - Saba Tasneem; Hafiz Ghufran; Maryam Azam; Amna Arif; Musab Bin Umair; Muhammad Amin Yousaf; Khurrum Shahzad; Azra Mehmood; Kausar Malik; Sheikh Riazuddin (Tissue Engineering and Regenerative Medicine, 2024)

State-of-the-art analysis of the fuel desulphurization processes: Perspective of CO2 utilization in coal biodesulphurization - Muhammad Ahmad; Maryam Yousaf; Jing-Cheng Han; Shafeeq Ur Rahman; Hafiz Muhammad Adeel Sharif; Linlin Wang; Zhaozhao Tang; Yang Zhou; Yuefei Huang (Chemical Engineering Journal, 2023)

Development of a new hybrid ensemble method for accurate characterization of future drought using multiple global climate models - Mahrukh Yousaf; Zulfiqar Ali; Muhammad Mohsin; Maryam Ilyas; Muhammad Shakeel (Stochastic Environmental Research and Risk Assessment, 2023)

Curcuminoids-enriched extract and its cyclodextrin inclusion complexes ameliorates arthritis in complete Freund’s adjuvant-induced arthritic mice via modulation of inflammatory biomarkers and suppression of oxidative stress markers - Uzma Saleem; Zunera Chauhdary; Zunaira Bakhtawar; Jawaher Alqahtani; Maryam Farrukh; Ifat Alsharif; Tourki A. S. Baokbah; Muhammad Ajmal Shah; Renald Blundell; Pharkphoom Panichayupakaranant (Inflammopharmacology, 2023)

A bioactive chalcone from the aerial parts of Indigofera conferta Gillet - Maryam Isah; Salima Murtala; Sakynah Musa Abdullahi; Asmau Nasiru Hamza; Nasir Tajuddeen; Mu’ammar Lawal Dauda; Vuyisa Mzozoyana; Aliyu Muhammad Musa (Natural Product Research, 2023)

Blockchain-enabled smart agriculture: Enhancing data-driven decision making and ensuring food security - Khalil Ur Rehman; Shahla Andleeb; Maryam Ashfaq; Nida Akram; Muhammad Waqar Akram (Journal of Cleaner Production, 2023)

Elucidating growth and biochemical characteristics of rice seedlings under stress from chromium VI salt and nanoparticles - Maryam Noor; Arif Ullah; Muhammad Israr Khan; Irum Raza; Muhammad Iqbal; Abdul Aziz; Gil Won Kim; Nadia Taimur; Azizullah Azizullah; Imran Ali; Pil Joo Kim (Environmental Science and Pollution Research, 2023)

Heavy metals in five commonly consumed fish species from River Swat, Pakistan, and their implications for human health using multiple risk assessment approaches - Kifayatullah Khan; Maria Zeb; Muhammad Younas; Hafiz Muhammad Adeel Sharif; Muhammad Yaseen; Abdullah G. Al-Sehemi; Yasar N. Kavil; Noor Samad Shah; Xianghui Cao; Afsheen Maryam; Muhammad Qasim (Marine Pollution Bulletin, 2023)

Case fatality rate and burden of snakebite envenoming in children – A systematic review and meta-analysis - Garba Iliyasu; Farouq M. Dayyab; Godpower C. Michael; Muhammad Hamza; Maryam A. Habib; José M. Gutiérrez; Abdulrazaq G. Habib (Toxicon, 2023)

Biosynthesized manganese oxide nanoparticles maintain firmness of tomato fruit by modulating soluble solids and reducing sugars under biotic stress - Maryam Anar; Mahnoor Akbar; Kinza Tahir; Hassan Javed Chaudhary; Muhammad Farooq Hussain Munis (Physiological and Molecular Plant Pathology, 2023)

Corrigendum to “Priming of adipose-derived stem cells with curcumin prior to cryopreservation preserves their functional potency: Towards an ‘Off-the-shelf’ therapy for burns” [Cryobiology 110 (2023) 69–78] - Maryam Azam; Hafiz Ghufran; Saba Tasneem; Azra Mehmood; Kausar Malik; Muhammad Amin Yousaf; Moazzam N. Tarar; Shehla Javed Akram; Sheikh Riazuddin (Cryobiology, 2023)

A Common Factor Analysis Based Data Mining Procedure for Effective Assessment of 21st Century Drought under Multiple Global Climate Models - Muhammad Ahmad; Zulfiqar Ali; Maryam Ilyas; Muhammad Mohsin; Rizwan Niaz (Water Resources Management, 2023)

Role of community-based conservation and natural resource management in building climate resilience among vulnerable mountain societies - Shameen Zafar; Muhammad Zafar Khan; Tahir Mehmood; Farida Begum; Maryam Sadiq (Climate and Development, 2023)

Strategic analysis on development of simultaneous adsorption and catalytic biodegradation over advanced bio-carriers for zero-liquid discharge of industrial wastewater - Jing-Cheng Han; Muhammad Ahmad; Maryam Yousaf; Shafeeq Ur Rahman; Hafiz Muhammad Adeel Sharif; Yang Zhou; Bo Yang; Yuefei Huang (Chemosphere, 2023)

Development of biocatalytic microbial ecosystem (FPUS@RODMs@In-PAOREs) for rapid and sustainable degradation of various refractory organics - Muhammad Ahmad; Maryam Yousaf; Jing-Cheng Han; Yuefei Huang; Yang Zhou; Zhaozhao Tang (Journal of Hazardous Materials, 2023)

Enhanced Degradation of Acid Orange 52 Using a Polyextremophilic Ascomycete in Stirred Tank Bioreactor - Qandeel Laraib; Maryam Shafique; Muhammad Ali Versiani; Khitab Gul; Uroosa Ejaz; Haji Muhammad; Sehar Afshan Naz; Drauzio E. N. Rangel; Alene Alder-Rangel; Kousar Yasmeen; Nusrat Jabeen; Jing Liu; et al. (Water, Air, & Soil Pollution, 2023)

Heavy Metal Occurrence, Pathways, and Associated Socio-ecological Risks in Riverine Water: Application of Geographic Information System, Multivariate Statistics, and Risk Assessment Models - Kifayatullah Khan; Muhammad Younas; Muhammad Sajawal Khan; Xu Li; Muhammad Fawad; Noor Samad Shah; Jafar Ali; Sana Ullah; Muhammad Ayaz; Afsheen Maryam; Asmat Ali; Akhtar Zeb Khan; et al. (Water, Air, & Soil Pollution, 2023)

Assessment of water quality, trace metal pollution, source apportionment and health risks in the groundwater of Chakwal, Pakistan - Maryam Batool; Muhammad Toqeer; Munir H. Shah (Environmental Geochemistry and Health, 2023)

Exploiting genetic diversity in enhancing phenotypic plasticity to develop climate-resilient cotton - Zulfiqar Ali; Hira Maryam; Muhammad Abu Bakar Saddique; Rao Muhammad Ikram (Genetic Resources and Crop Evolution, 2023)

Assessment of formulation variables of poor water soluble diacerein for its improved loading and anti-inflammatory activity - Maryam Shabbir; Kashif Barkat; Muhammad Umer Ashraf; Uzair Nagra; Syed Nisar Hussain Shah (Drug Delivery and Translational Research, 2023)

Discrimination of lithofacies in tight gas reservoir using field-specific rock physics modeling scheme. A case study from a mature field of middle Indus Basin, Pakistan - Muhammad Zahid Afzal Durrani; Syed Atif Rahman; Maryam Talib; Bakhtawer Sarosh (Acta Geophysica, 2023)

Factors associated with foot-and-mouth disease seroprevalence in small ruminants and identification of hot-spot areas in northern Nigeria - Mattia Begovoeva; David O. Ehizibolo; Adeyinka J. Adedeji; Moses O. Oguche; Olumuyiwa Oyekan; Sandra I. Ijoma; Rebecca B. Atai; Yiltawe Wungak; Banenat B. Dogonyaro; David D. Lazarus; Mark Samson; Hussaini Ularamu; et al. (Preventive Veterinary Medicine, 2023)

Priming of adipose-derived stem cells with curcumin prior to cryopreservation preserves their functional potency: Towards an ‘Off-the-shelf’ therapy for burns - Maryam Azam; Hafiz Ghufran; Saba Tasneem; Azra Mehmood; Kausar Malik; Muhammad Amin Yousaf; Moazzam N. Tarar; Shehla Javed Akram; Sheikh Riazuddin (Cryobiology, 2023)

The curative and mechanistic acumen of curcuminoids formulations against haloperidol induced Parkinson’s disease animal model - Uzma Saleem; Sundas Khalid; Zunera Chauhdary; Fareeha Anwar; Muhammad Ajmal Shah; Ifat Alsharif; Ahmad O. Babalghith; Rana O. Khayat; Aishah E. Albalawi; Tourki A. S. Baokbah; Maryam Farrukh; Celia Vargas-De-La-Cruz; et al. (Metabolic Brain Disease, 2023)

Formulation of heterometallic ZIF-8@Cu/Ni/ZnO@CNTs heterostructure photocatalyst for Ultra-Deep desulphurization of coal and fuels - Muhammad Ahmad; Maryam Yousaf; Weiwei Cai; Zhi-Ping Zhao (Chemical Engineering Journal, 2023)

Morphophysiological responses of sweet basil (Ocimum basilicum L.) to the nickel stress and inoculation with Pseudomonas strains - Marzieh Davoudi; Behrooz Esmaielpour; Gholamreza Gohari; Ali Ashraf Soltani Toolarood; Morteza Sheikhalipour; Hamideh Fatemi; Maryam Haghighi; Muhammad Farooq (Acta Physiologiae Plantarum, 2023)

Success of Aquaculture Industry with New Insights of Using Insects as Feed: A Review - Amna Hameed; Waqar Majeed; Muhammad Naveed; Uzma Ramzan; Matteo Bordiga; Maryam Hameed; Saud Ur Rehman; Naureen Rana (Fishes, 2022)
Most of world’s fish and seafood are produced by aquaculture, which is one of the biggest contributors to the world’s food security. The substantial increase in prices of conventional feed ingredients and the over-exploitation of natural resources are some of the biggest constraints to aquaculture production. To overcome this stress, different approaches and techniques are used, among which the use of non-conventional feed ingredients in the aquaculture sector is the most recent approach. Different non-conventional feed ingredients such as plant-based products, algae (both micro and macroalgae), single-cell protein (bacteria and yeast), and insect meal are currently used in aquaculture for sustainable food production. Amongst all these novel ingredients, insects have greater potential to replace fishmeal. The existence of about 1.3 billion tons of food and agriculture waste from the food chain supply poses a serious environmental threat. Insects are tiny creatures that can thrive on organic waste and thus can convert the waste to wealth by the bioconversion and nutritional upcycling of organic waste. Insects have the potential to recover nutrients from waste aquaculture products, and many fish species feed on insects naturally. Therefore, employing insects in the aquaculture sector to replace fishmeal is an eco-friendly approach. The present review briefly highlights emerging non-conventional feed ingredients, with special attention given to insects. The current review also focuses on the nutritional value of insects, factors affecting the nutritional value of insects, potential insects that can be employed in the aquaculture sector, the physiological response of fish when fed with insect meal, techno-functional properties of insect meal, and emerging approaches for addressing possible downsides of employing insect meal in fish diets. Finally, it suggests avenues for further research into these inventive fishmeal replacements.

Pharmacological potential of Sargassum sp. of west coast of Maharashtra Kunkeshwar, India - Gholamreza Abdi; Vanita Chandrashekhar Karande; Arifullah Mohammed; Maryam Abbasi Tarighat; Khang Wen Goh; Zulhisyam Abdul Kari; Lee Seong Wei; Muhammad Rajaei Ahmad Mohd Zain; Mehdi Mohammadi; Gaik Ee Lee; Mukul M. Barwant (Frontiers in Marine Science, 2022)
A promising plant group that is important in medicine is the seaweed. In this investigation, we have focused on the pharmacological prospects of brown algae ( Sargassum sp ). Nutraceuticals refer to products that may combine pharmacological and nutrition. We have collected the plant material close to Kunkeeshwar in Sindhudurg, Maharashtra’s western coast. We focused on the Physicochemical Attributes of Sargassum sp., and the study found that the ash value (41 ± 0.67), moisture content (1.33 ± 0.038), alcohol-soluble extractive value (1.5 ± 0.030), moisture content (1.33 ± 0.038), and total cash value (41 ± 0.67) are all stated in (%).The GCMS findings, which demonstrate that a total of 25 chemicals were discovered in the aqueous extract of Sargassum sp., also represent their nutritional profile. All of these substances have chromatograms that can be observed.1-Hexyl-2-nitrocyclohexane is the substance with the second-largest retention duration and relative areas, followed by n-hexadanoic acid. The presence of ocladecanoic acid was later determined. The explanation for how the activity is concentration-dependent is pharmacological activity, particularly antioxidant activity as shown by the DPPH assay.2μg/mL is -1545.4 ± 0.05. as a minimum. and at (32 g/mL is 7.67 ± 0.05) is the highest. The antifungal activity of Candida albicans (12.8 mm) and Aspergillus niger (14.4 mm) both exhibit zone inhibition when tested against two distinct pathogen however, the antibacterial activity of three different bacteria demonstrates that Staphylococcus aureus (12 mm), Bacillus subtilis (10 mm), Proteus mirabilis (12.8 mm), and Escherichia. coli are all zone inhibited (13mm). Brown algae offer the greatest potential for human health nutrition, while pharmacological analysis is helpful for therapeutic application, according to the overall analysis.

Trehalose: a promising osmo-protectant against salinity stress—physiological and molecular mechanisms and future prospective - Muhammad Nawaz; Muhammad Umair Hassan; Muhammad Umer Chattha; Athar Mahmood; Adnan Noor Shah; Mohamed Hashem; Saad Alamri; Maria Batool; Adnan Rasheed; Maryam A. Thabit; Haifa A. S. Alhaithloul; Sameer H. Qari (Molecular Biology Reports, 2022)

Genetic diversity and population structure assessed through simple sequence repeat markers in Saccharum spp. hybrids from Pakistan and Sri Lanka - Sundas Shahzad; Muhammad Saeed; Shagufta Perveen; Muhammad Azeem; Iqra Sajjad; Shazia Saeed; Muhammad Naeem; Alia Javed; Iqra Sultan; Ukasha Faria; Sana Maryam; Muhammad Zaid Yousaf (Genetic Resources and Crop Evolution, 2022)

Cytotoxic and genotoxic evaluation of bisphenol S on onion root tips by Allium cepa and comet tests - Muhammad Muddassir Ali; Areej Fatima; Sadia Nawaz; Abdul Rehman; Maryam Javed; Asif Nadeem (Environmental Science and Pollution Research, 2022)

Analyzing the determinants of sustainability of China Pakistan Economic Corridor (CPEC) projects: an interpretive structural modelling (ISM) approach - Maryam Farooq; Zia-ur-Rehman Rao; Muhammad Shoaib (Environmental Science and Pollution Research, 2022)

Dye Wastewater Treatment Using Wheat Straw Biochar in Gadoon Industrial Areas of Swabi, Pakistan - Muhammad Tariq; Shams Ali Baig; Dilawar Farhan Shams; Sayed Hussain; Rahib Hussain; Abdul Qadir; Hafiza Seerat Maryam; Zia Ullah Khan; Shehla Sattar; Xinhua Xu (Water Conservation Science and Engineering, 2022)

Heavy metal pollution in the soil of a riverine basin: distribution, source, and potential hazards - Kifayatullah Khan; Abdul Mohsin; Hafiz Muhammad Adeel Sharif; Afsheen Maryam; Jafar Ali; Xu Li; Sobhy Mostafa Ibrahim; Muhammad Ayaz; Yunqiao Zhou; Muhammad Younas (Environmental Monitoring and Assessment, 2022)

Quantitative characterization of unconventional (tight) hydrocarbon reservoir by integrating rock physics analysis and seismic inversion: a case study from the Lower Indus Basin of Pakistan - Maryam Talib; Muhammad Zahid Afzal Durrani; Arshad Hussain Palekar; Bakhtawer Sarosh; Syed Atif Rahman (Acta Geophysica, 2022)

CRISPR/Cas9 is a powerful tool for precise genome editing of legume crops: a review - Adnan Rasheed; Aminah A. Barqawi; Athar Mahmood; Muhammad Nawaz; Adnan Noor Shah; Daniyah H. Bay; Maryam A. Alahdal; Muhammad Umair Hassan; Sameer H. Qari (Molecular Biology Reports, 2022)

GhCDNC and GhCYP706B1 genes mediate gossypol biosynthesis in upland cotton - Hira Maryam; Zulfiqar Ali; Muhammad Abu Bakar Saddique; Fahim Nawaz (Molecular Biology Reports, 2022)

Modelling Climate Uncertainty and Adaptations for Soybean-Based Cropping System - Maryam Ejaz; Ghulam Abbas; Zartash Fatima; Pakeeza Iqbal; Muhammad Ali Raza; Ahmed M. S. Kheir; Mukhtar Ahmed; Khair Muhammad Kakar; Shakeel Ahmad (International Journal of Plant Production, 2022)

Integrating green business strategies and green competencies to enhance green innovation: evidence from manufacturing firms of Pakistan - Salman Yahya; Adnan Khan; Maryam Farooq; Muhammad Irfan (Environmental Science and Pollution Research, 2022)

Porostereum spadiceum-AGH786 Regulates the Growth and Metabolites Production in Triticum aestivum L. Under Salt Stress - Syeda Leeda Gul; Yong-Sun Moon; Muhammad Hamayun; Sumera Afzal Khan; Amjad Iqbal; Muhammad Aaqil Khan; Anwar Hussain; Maryam Shafique; Yoon-Ha Kim; Sajid Ali (Current Microbiology, 2022)

Endophytic aspergillus oryzae reprograms Abelmoschus esculentus L. to higher growth under salt stress via regulation of physiochemical attributes and antioxidant system - Farzana Gul Jan; Nusrat bibi; Muhammad Hamayun; Yong-Sun Moon; Gul Jan; Maryam Shafique; Sajid Ali (Biologia, 2022)

Sarcococca saligna extract attenuates formaldehyde-induced arthritis in Wistar rats via modulation of pro-inflammatory and inflammatory biomarkers - Maryam Farrukh; Uzma Saleem; Muhammad Qasim; Maria Manan; Muhammad Ajmal Shah (Inflammopharmacology, 2022)

High-fat diet intake ameliorates the expression of hedgehog signaling pathway in adult rat liver - Rabia Mehmood; Nadeem Sheikh; Muhammad Babar Khawar; Muddasir Hassan Abbasi; Maryam Mukhtar (Molecular Biology Reports, 2022)

Systematic analysis of HD-ZIP transcription factors in sesame genome and gene expression profiling of SiHD-ZIP class I entailing drought stress responses at early seedling stage - Maryam Mehmood; Muhammad Jadoon Khan; Muhammad Jawad Khan; Nadeem Akhtar; Fizza Mughal; Syed Tahir Abbas Shah; Muhammad Zeeshan Hyder; Sumaira Farrakh; Irfan Sadiq (Molecular Biology Reports, 2022)

Biological Evaluation of Synthesized Schiff Base-Metal Complexes Derived from Sulfisomidine - Amina Mumtaz; Tariq Mahmud; Maryam Khalid; Huma Khan; Aatika Sadia; Malka M. Samra; Muhammad Asim Raza Basra (Journal of Pharmaceutical Innovation, 2022)

Prevalence, epidemiology, seasonality, and phylogeny of Anaplasma marginale in blood samples of goats collected from Punjab, Pakistan - Muhammad Naveed Aziz; Muhammad Irfan; Asia Parveen; Muhammad Asif; Maryam Ijaz; Sadia Mumtaz; Sezayi Ozubek; Munir Aktas; Rana Khalid Iqbal; Furhan Iqbal (Tropical Animal Health and Production, 2022)

Cyperus iria aqueous-ethanol extract ameliorated hyperglycemia, oxidative stress, and regulated inflammatory cytokines in streptozotocin-induced diabetic rats - Myeda Saeed; Ali Sharif; Saeed Ul Hassan; Bushra Akhtar; Faqir Muhammad; Maryam Malik (Environmental Science and Pollution Research, 2022)

Genetic basis of some physiological traits and yield in early and late sowing conditions in bread wheat (Triticum aestivum L.) - Mian Abdur Rehman Arif; Maryam Liaqat; Muhammad Imran; Muhammad Qandeel Waheed; Anjuman Arif; Sukhwinder Singh; Sajid Shokat (Journal of Applied Genetics, 2021)

Determinants and implications of environmental practices for waste management and the minimization in the construction industry: a case study of Pakistan - Ahsan Riaz Khan; Allah Ditta; Muhammad Sajid Mehmood; Zheng MaoSheng; Maryam Natalia (Environmental Science and Pollution Research, 2021)

Molecular detection and prevalence of Theileria ovis and Anaplasma marginale in sheep blood samples collected from Layyah district in Punjab, Pakistan - Kainat Abid; Sundas Bukhari; Muhammad Asif; Ayesha Sattar; Maryam Arshad; Munir Aktas; Sezayi Ozubek; Rehan Sadiq Shaikh; Furhan Iqbal (Tropical Animal Health and Production, 2021)

Clostridium culturomicium sp. nov. and Clostridium jeddahitimonense sp. nov., novel members of the Clostridium genus isolated from the stool of an obese Saudi Arabian - Hoang Thong Kieu; Noémie Garrigou; Amael Fadlane; Ludivine Brechard; Nicholas Armstrong; Philippe Decloquement; Muhammad Yasir; Esam Ibraheem Azhar; Saad B. Al-Masaudi; Jean-Christophe Lagier; Maryam Tidjani Alou; Didier Raoult (Current Microbiology, 2021)

Pomegranate as a source of bioactive constituents: a review on their characterization, properties and applications - Maryam Pirzadeh; Nicola Caporaso; Abdur Rauf; Mohammad Ali Shariati; Zhanibek Yessimbekov; Muhammad Usman Khan; Muhammad Imran; Mohammad S. Mubarak (Critical Reviews in Food Science and Nutrition, 2021)

An integrated multi-objective optimization modelling for sustainable development goals of India - Irfan Ali; Umar Muhammad Modibbo; Jahangir Chauhan; Maryam Meraj (Environment, Development and Sustainability, 2021)

Rabies virus infection in mice up-regulates B7-H1 via epigenetic modifications - Comfort E. Ojedapo; Aliyu Muhammad; Grace S. N. Kia; Musa M. Abarshi; Maryam Abdulazeez; Joy Cecilia Atawodi; Jacob K. P. Kwaga (VirusDisease, 2020)

Microfacies analysis, diagenetic overprints, geochemistry, and reservoir quality of the Jurassic Samanasuk Formation at the Kahi Section, Nizampur Basin, NW Himalayas, Pakistan - Emad ullah Khan; Maryam Saleem; Abbas Ali Naseem; Waqar Ahmad; Muhammad Yaseen; Tehseen Ullah Khan (Carbonates and Evaporites, 2020)

Induction of Rabies Virus Infection in Mice Brain may Up and Down Regulate Type II Interferon gamma via epigenetic modifications - Maryam Abdulazeez; Grace S. N. Kia; Musa M. Abarshi; Aliyu Muhammad; Comfort E. Ojedapo; Joy Cecilia Atawodi; David Dantong; Jacob K. P. Kwaga (Metabolic Brain Disease, 2020)

Photocatalytic degradation and kinetic modeling of azo dye using bimetallic photocatalysts: effect of synthesis and operational parameters - Nadia Riaz; Maryam Hassan; Maria Siddique; Qaisar Mahmood; Umar Farooq; Rizwana Sarwar; Muhammad Saqib Khan (Environmental Science and Pollution Research, 2020)

Association of rs146292819 Polymorphism in ABCA1 Gene with the Risk of Coronary Artery Disease in Pakistani Population - Maryam Sameem; Asima Rani; Muhammad Arshad (Biochemical Genetics, 2019)

Development and Evaluation of Optimized Thiolated Chitosan Proniosomal Gel Containing Duloxetine for Intranasal Delivery - Maryam khatoon; Muhammad Farhan Sohail; Gul Shahnaz; Fiza ur Rehman; Fakhar-ud-Din; Asim ur Rehman; Naseem Ullah; Umair Amin; Gul Majid Khan; Kifayat Ullah Shah (AAPS PharmSciTech, 2019)

N-Pyrazoloyl and N-thiopheneacetyl hydrazone of isatin exhibited potent anti-inflammatory and anti-nociceptive properties through suppression of NF-κB, MAPK and oxidative stress signaling in animal models of inflammation - Sara Zeeshan; Muhammad Naveed; Adnan Khan; Ayesha Atiq; Maryam Arif; Muhammad Naeem Ahmed; Yeong Shik Kim; Salman Khan (Inflammation Research, 2019)

Characteristics of pipe corrosion scales in untreated water distribution system and effect on water quality in Peshawar, Pakistan - Dilawar Farhan Shams; Saeed Islam; Baoyou Shi; Waliullah Khan; Buddhika Gunawardana; Maryam Saad; Muhammad Qasim; Haider Ali Javed; Sahib Gul Afridi; Muhammad Naeem; Gul Shahzada Khan (Environmental Science and Pollution Research, 2019)

Redox balance and DNA fragmentation in arsenic-exposed occupational workers from different industries of Pakistan - Maryam Raza; Ishrat Mahjabeen; Muhammad Fahim; Waqar Ahmad Malik; Asad Ullah Khan; Mahmood Akhtar Kayani; Ayesha Khan; Zertashia Akram (Environmental Science and Pollution Research, 2018)

Prevalence of selected pharmaceuticals in surface water receiving untreated sewage in northwest Pakistan - Aisha Khan; Dilawar Farhan Shams; Waliullah Khan; Aamir Ijaz; Muhammad Qasim; Maryam Saad; Ayesha Hafeez; Shams Ali Baig; Nisar Ahmed (Environmental Monitoring and Assessment, 2018)

Osteopontin gene polymorphism association with milk traits and its expression analysis in milk of riverine buffalo - Sidra Manzoor; Asif Nadeem; Javed Maryam; Abu Saeed Hashmi; Muhammad Imran; Masroor Ellahi Babar (Tropical Animal Health and Production, 2018)

Preference and performance of Plutella xylostella (L.) (Lepidoptera: Plutellidae) on canola cultivars - Seyed Ali Asghar Fathi; Maryam Bozorg-Amirkalaee; Rana Muhammad Sarfaraz (Journal of Pest Science, 2011)